Response Surface Methodology for Optimization of Microbial Electrolysis Cell Performance Using Carbon Nanotube-Based Cathode - Yee, Jing Xuan (Progress in Engineering Application and Technology, 2021)
Hydrogen gas is a promising clean energy carrier and alternative renewable energy. Microbial electrolysis cell (MEC) is a new biological process that converts low-grade organics from wastewater to hydrogen gas. The MEC performance can largely be affected by the cathode material and applied voltage. Thus, this study was conducted to obtain the optimum operational conditions of polyaniline/multi-walled carbon nanotube (PANI/MWCNT) cathode and applied voltage for the hydrogen production efficiency in MEC by using the application of response surface methodology (RSM). ANOVA was used to evaluate the mathematical and statistical analysis to validate the regression model via historical data design. The independent parameters used were applied voltage and different weight percent of PANI/MWCNT cathode, while the responses were hydrogen production rate (HPR), coulombic efficiency (CE), cathodic hydrogen recovery (rcat) and energy recovery (ER) of MEC. The results showed the optimum condition was by using 75 wt. % PANI/MWCNT cathode at an applied voltage of 1.0V with responses of 1.06 m3/m3/day HPR, 48.0% CE, 57% rcat and 90% ER, whereas the predicted values were 1.08 m3/m3/day HPR, 47.8% CE, 57.9% rcat and 91% ER. Overall, RSM has proved to be a reliable optimization technique that can be used to design experiments and determine the performance of MEC.